(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Achieving equitable outcomes in mathematics instruction is a lofty but elusive goal, as evidenced by standardized test results and representation in high-level courses. The role of teacher bias in choice of instructional materials and implementation requires strategic examination and corrective action in order for an individual teacher to begin pursuing equity in the classroom. Problem-based curriculum is a step towards using high-quality instruction to ensure that all students have access to challenging math and the support they need to succeed. A closer look at a teacher’s implementation of such curriculum illuminates the teacher practices needed to promote equity within the framework of a problem-based instructional model.